Ambient fine particulate pollution associated with diabetes mellitus among the elderly aged 50 years and older in China. (December 2018) - Yang, Yin; Guo, Yanfei; Qian, Zhengmin (Min); Ruan, Zengliang; Zheng, Yang; Woodward, Alistair; Ai, Siqi; Howard, Steven W.; Vaughn, Michael G.; Ma, Wenjun; Wu, Fan; Lin, Hualiang
Abstract: The linkage between ambient air pollution exposure and occurrence of diabetes mellitus is not well defined. This study examined the association between exposure to fine particles (PM2.5 ) and the prevalence of diabetes among Chinese elderly people. We surveyed 11, 504 adults aged ≥50 years in China, estimated the annual concentrations of ambient PM2.5 using a satellite-based model of aerosol optical depth information. We employed a generalized mixed effects model to examine the association between PM2.5 and the prevalence of diabetes and explored potential effect modifiers. We estimated diabetes burden attributable to ambient PM2.5 if the observed association is indeed causal. The diabetes prevalence among the participants was 6.5% (n = 745). Our analysis found a statistically significant association between PM2.5 and diabetes. The adjusted odds ratio was 1.27 (95% confidence interval (CI), 1.12, 1.43) for each 10 μg/m 3 increment in ambient PM2.5 . Stratified analyses found a lower association among the participants with higher consumption of fruit. We estimated that 22.02% (95% CI: 8.59%, 43.29%) of the diabetes cases could be ascribable to ambient PM2.5 . Our finding suggests that PM2.5 exposures could increase the risk of diabetes, and if causal, could be responsible for substantial burden of diabetes among the Chinese elderly; and higher intakes of fruit might reduce the harmful effects of PM2.5, however, due to the limitation of the cross-sectional study design, more studies are warranted to confirm this observation. Graphical abstract: Image 1 Highlights: We examined the association between PM2.5 and diabetes in Chinese adults. Annual PM2.5 was estimated using satellite data at a 1*1 km resolution. Each 10 μg/m 3 increment in PM2.5 was associated with 27% increase in diabetes. 22% of diabetes cases could be attributable to ambient PM2.5 Abstract : Ambient fine particulate pollution is associated with diabetes.